2021
DOI: 10.1371/journal.pone.0257479
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity, antimicrobial and antioxidant activities of mosses obtained from open habitats

Abstract: Mosses are mainly the object of ecological and taxonomic research. This group of plants are still underestimated by scientists in other aspects of research. Recent research has shown that these plants contain remarkable and unique substances with high biological activity. Five species of mosses from a large urban ecosystem were identified for present study. In order to determine their biological potential, multifaceted studies were carried out, including: total phenolics content, antioxidant activity, antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Although a higher number of methanogenesis‐related genes were detected at 35°C (Figure 3f), the suppressed activity of methanogens and low CH 4 production rate at 35°C could further be explained by the enhanced accumulation of phenolic constituents with antimicrobial and pH‐controlling properties. Previously, Wolski et al, 2021 demonstrated the inhibition of microbial activity in ecosystems with high phenolic contents. Moreover, the antimicrobial properties of Sphagnum ‐derived polyphenolics have been previously established by (Fudyma et al, 2019; Mellegård et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although a higher number of methanogenesis‐related genes were detected at 35°C (Figure 3f), the suppressed activity of methanogens and low CH 4 production rate at 35°C could further be explained by the enhanced accumulation of phenolic constituents with antimicrobial and pH‐controlling properties. Previously, Wolski et al, 2021 demonstrated the inhibition of microbial activity in ecosystems with high phenolic contents. Moreover, the antimicrobial properties of Sphagnum ‐derived polyphenolics have been previously established by (Fudyma et al, 2019; Mellegård et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, birds' preferences for specific bryophyte species may be related to their production of secondary metabolites with antimicrobial, antifungal, or antibacterial bioactivity (Horn et al, 2021;Klavina et al, 2015) (Nikolajeva et al, 2012;Veljić et al, 2008;Wolski et al, 2021).…”
Section: Selective Choice Of Bryophytes By Great Titsmentioning
confidence: 99%
“…The vast majority of the research has focused on the in vitro antioxidant activity of bryophytes extracts and pure isolated compounds through multiple chemical methods such as 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABST) assay, lipid peroxidation test (LPT), β-carotene assay (Tables 1 and 2) (for in-depth methodological review read [25]) [26][27][28][29][30][31][32][33]. The extraction methods mostly rely on solvents such as ethanol, methanol, water, and acetone which are the most common solvents used for in vitro antioxidant testing [25].…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Extracts, depending on the solvent used and the selected species contain variable concentrations of phenolics, polyphenols, bibenzyls and terpenoids which are responsible for the antioxidant activity (Tables 1 and 2). A study of [31] that focused on the chemical composition of pure ethanol extracts, revealed the presence of several glycosidic flavonoids (e.g., apigenin hexoside, kaempferol 3-galactoside). Another study obtained similar results from water:ethanol extracts of several moss species [34].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation